Help for the Workers of Spain Fund: contributions received to 10th August 1936
028-0001-001 HELP FOR THE WORKERS OF SPAIN FUND. Contributions Received to 10th August, 1936. £ s d Trades Unions. 1952.12. 3 Trades Councils & Labour Parties. 133. 9.11 Individual & Other Subscriptions. 2330.10. 1 £4416.12. 3 LK/10th August, 1936. 292/946/28/1